Extended Lateral Orbital Craniotomy: Anatomic Study and Initial Clinical Series of a Novel Minimally Invasive Pterional Approach - Sattur, Mithun G.; Abi-Aad, Karl R.; Welz, Matthew E.; Aoun, Rami James; Krishna, Chandan; Purnell, Chad; Alghoul, Mohammed; Bendok, Bernard R. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Of the minimally invasive “keyhole” alternatives to the pterional region, the supraorbital eyebrow approach is the most widely adopted. Yet it can prove disadvantageous when a more direct lateral microsurgical trajectory of attack to the Sylvian fissure and anterior middle fossa are needed.Objective The extended lateral orbital (XLO) approach was designed to be direct and minimally invasive, with the sphenoid ridge at the center of exposure.Methods Five injected cadaver heads were used for anatomic study of the XLO approach. The anatomic course of the frontalis branch of facial nerve was studied in relation to the XLO incision. Following XLO incision, the bone exposure was measured. The intracranial microsurgical exposure was assessed subjectively. Application of the technique in representative clinical operative cases is provided.Results The frontalis nerve was protected in the subgaleal fat pad, with an average minimum distance of 2.3 cm from the XLO incision. The mean calvarial area exposure was 4.95 cm2 and consistently centered on the sphenoid ridge. Excellent access to ipsilateral Sylvian's fissure, perisylvian regions, and supra-/parasellar structures was possible. The main limitations related to exposure of the posterior Sylvian fissure and the expected limitations of microsurgical instrument manipulation from a smaller craniotomy.Conclusions The XLO approach is a minimally invasive keyhole approach to the pterional region that affords a unique lateral trajectory via a craniotomy centered on the sphenoid ridge. Excellent exposure to properly selected lesions is possible. The incision is at a safe distance from the frontalis branch and shows excellent cosmetic healing.
Keywords: minimally invasive craniotomy; pterional keyhole approach; middle cerebral artery aneurysm; sphenoid ridge; micro surgical clipping; frontalis branch of facial nerve; Sylvian fissure